Palladium-Catalyzed Carbonylation of Azides and Mechanistic Studies - Feng, Jiyao; Zhang, Zhen; Li, Xuefeng; Zhang, Zhenhua (Synlett, 2020)
Isocyanates are widely applied in the fields of materials science, drug discovery and chemical industry processes. Palladium-catalyzed carbonylation of azides with carbon monoxide (CO) is reported as a powerful method for simple and efficient access to isocyanates, which are important precursors for preparing structurally meaningful urea, carbamate and amidine derivatives. In this account, we provide an overview on the synthesis of isocyanates and their subsequent reactions to obtain diverse nucleophilic addition products. In addition, with particular emphasis on our mechanistic studies of the Pd-catalyzed carbonylation process, we outline the identification of the actual catalytic species, the possible intermediates and some key factors in the catalytic cycle.1 Introduction2 Palladium-Catalyzed Reaction of Azides with CO and Subsequent Nucleophilic Additions3 Mechanistic Studies on the Palladium-Catalyzed Reaction of Azides with CO3.1 Studies on the Actual Catalytic Species and the Key Intermediates in the Activation and Carbonylation of Acyl Azides3.2 Study of the Sulfonylurea Product Self-Catalyzed Carbonylation of Sulfonyl Azides3.3 Study of the Actual Catalytic Pattern of the Pd/C Catalyst4 Conclusion
Keywords: azides; isocyanates; palladium catalysts; carbon monoxide; ureas